Analisis Strategi Pemasaran Product, Price, Place, Promotion (4p) Airish Hotel Palembang Dalam Meningkatkan Daya Tarik Konsumen - Alfin Renaldi; M. Miftah Farid (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
As the number of hotels increases and customer demands diversify, the hotel industry in Palembang City is experiencing increasingly fierce competition. In this situation, every hotel must use appropriate and integrated marketing strategies to maintain its existence and increase customer appeal. As a three-star hotel in the area, Airish Hotel Palembang uses a four P marketing mix strategy, which includes product, price, place, and promotion. Based on the results of an internship focused on marketing communications, this study examines the application of the 4Ps marketing concept at Airish Hotel Palembang. This study uses a descriptive qualitative approach. Data were collected through direct observation, examination of internal hotel documentation, and secondary data searches from official and reliable sources during the period 2022–2025. The results of the study indicate that Airish Hotel Palembang has consistently used the 4Ps marketing strategy. This strategy includes creating service products and facilities that are in line with the market segment, setting competitive prices, using the hotel's location and physical facilities as added value, and prioritizing customer experience and satisfaction in promotional activities. Building a positive image and increasing customer attraction to Airish Hotel Palembang is aided by the use of this marketing mix. It is hoped that this study will become an academic and practical reference for.